The selective inhibition of the Syk tyrosine kinase ameliorates experimental autoimmune arthritis - Káposztás, Eszter; Balogh, Lili; Mócsai, Attila; Kemecsei, Éva; Jakus, Zoltán; Németh, Tamás (Frontiers in Immunology, 2023)
Autoimmune arthritis – such as rheumatoid arthritis – affect a significant proportion of the population, causing everyday joint pain, decreased mobility and reduced quality of life. Despite having more and more therapeutic options available, there are still a lot of patients who can not reach remission or low disease activity by current therapies. This causes an urgent need for the development of new treatment options. The Syk tyrosine kinase plays an essential role in B cell receptor, Fc receptor and integrin signaling. It has been shown that the hematopoietic cell-specific deletion of Syk resulted in a complete protection against autoantibody-induced experimental arthritis. This prompted us to test the effect of entospletinib, a second generation, Syk-selective inhibitor, which has a tolerable safety profile according to hematological clinical trials, in experimental autoimmune arthritis. We found that entospletinib dose-dependently decreased the macroscopic signs of joint inflammation, while it did not affect the health status of the animals. In line with these findings, local neutrophil accumulation and cytokine levels were reduced compared to the vehicle-treated group, while macrophage accumulation and synovial fibroblast numbers were not significantly altered. Meanwhile, entospletinib dose-dependently decreased the cell responses of immune complex- or integrin ligand-activated neutrophils. Overall, we found that selective Syk inhibition by entospletinib reduced the activity of autoantibody-induced experimental arthritis, which seems to be based mainly on the effect of the inhibitor on neutrophil functions. Our data raise the possibility that entospletinib could be a good drug candidate in the treatment of human autoimmune arthritis.